Novel synthetic approach for designing metal-free, redox-active quinoxaline-benzimidazole-based organic polymers with high energy storage capacity - Salunkhe, Pravin S.; Patil, Yuvraj S.; Dhole, Indrajeet A.; Kalshetti, Basavraj S.; Patil, Vikas B.; Mane, Shivshankar R.; Ghanwat, Anil A. (New Journal of Chemistry, 2019)
New organic framework materials, namely, polyphenylquinoxaline (QOP) and polyphenylquinoxaline-benzimidazole (QOP-BOP) were designed using a high-temperature (>100 degrees C) polymerization reaction with different monomers, i.e., 2,5-bis-[(4-benzoylcarbonyl)phenyl]-3-4 diphenyl thiophene (BbcPDT), aromatic tetraamines and biphenyl dicarboxylic acid. The QOP-BOP copolymer exhibited specific capacitance (SC) of 305 F g(-1) at the current density of 2 A g(-1) and 88% retention of its initial specific capacitance after 1000 cycles, which resulted in good cyclic stability. This work establishes the first use of thiophene integrated with quinoxaline-benzimidazole units for energy storage applications and provides strategies for further developments in the performance of such conjugated materials. Cyclic voltammetry, charge-discharge and electrochemical impedance techniques were used to evaluate the electrochemical parameters, which demonstrated their potential in future energy storage devices.

Synthesis of novel of 2, 5-disubstituted 1, 3, 4-oxadiazole derivatives and their in vitro anti-inflammatory, anti-oxidant evaluation, and molecular docking study - Kashid, Bharat B.; Salunkhe, Pravin H.; Dongare, Balasaheb B.; More, Kishor R.; Khedkar, Vijay M.; Ghanwat, Anil A. (Bioorganic & Medicinal Chemistry Letters, 2020)
A series of novel 2, 5-disubstituted 1, 3, 4-Oxadiazole derivatives as a potential anti-inflammatory, and antioxidant agent were synthesized via cyclisation. Hydrazide molecule treated with substituted acids in the presence of phosphorus oxychloride (POCl3) as an efficient reagent as well as solvent by conventional method with shorter reaction time and excellent yield. The newly synthesized 1, 3, 4-oxadiazole derivatives exhibited excellent to good anti-inflammatory and anti-oxidant activities compaired to the standard drugs. Molecular docking study on the crucial anti-inflammatory target-cyclooxygenase-2 (COX-2) revealed the ability of the scaffold to correctly recognize the active site and achieve significant bonded and non-bonded interactions with key residues therein. This study could identify potential compounds which can be pertinent starting points for structure-based drug design to obtain newer anti-inflammatory agents.
Keywords: 1; 3; 4-Oxadiazole; Anti-inflammatory; Anti-Oxidant; Biological activity; computational chemistry